Accounting for breakout in Britain: The industrial revolution through a Malthusian lens - Alexander Tepper; Karol Jan Borowiecki (Federal Reserve Bank of New York, 2013)
This paper develops a simple dynamic model to examine the breakout from a Malthusian economy to a modern growth regime. It identifies several factors that determine the fastest rate at which the population can grow without engendering declining living standards; this is termed maximum sustainable population growth. We then apply the framework to Britain and find a dramatic increase in sustainable population growth at the time of the Industrial Revolution, well before the beginning of modern levels of income growth. The main contributions to the British breakout were technological improvements and structural change away from agricultural production, while coal, capital, and trade played a minor role.
Keywords: N13; N33; O1; O41; O52; 330; Industrial Revolution; Malthusian dynamics; maximum sustainable population growth; development; demographics